Formulasi Metode Pengasuhan Santri pada Pondok Pesantren Al-Junaidiyah Biru Bone dalam Menangkal Pemikiran Radikalisme - Irfan Rahim, Irfan (JURNAL AL-QAYYIMAH, 2020)
This article discusses the formulation of students parenting methods at Pondok Pesantren Al-Junaidiyah Biru Bone in the ward of the thought of radicalism. This research is categorized as qualitative descriptive research. The data source is taken from the subject of research, in this case some parties involved in the implementation of religious humanism include: leadership of Pesantren, Pembina, teachers and students. The results showed that Al-Junaidiyah pesantren Biru Bone adopted a pattern of democratic parenting, authoritarian, and into in turn depending on the situation and conditions faced by the caregiver against the Santrinya. When caregivers give teaching, the caregiver is more inclined to use a democratic pattern, if the sitter gives the punishment due to the students commit violations, then the caregivers are more dominant to apply an authoritarian pattern, and when the caregiver gives the fertilmaker to do good to the students then the caregivers apply a PersuIn implementing the anticipation of radicalism, Pesantren Al-Junaidiyah Biru Bone made efforts that can generally be said equal and in line with the activities of the Ministry of Religion. Socialization of Islam as a moderate religion. Besides the Pesantren Al-Junaidiyah Biru Bone made special efforts such as; Setting strict lesson hours so that the space for the dissemination of radicalism can be anticipated, realization of the applicable rules must be applied to the good, prohibition on using HP, radio, supervision at the time of watching television, students must be diasramakan and pickup must be done by the family on holidays, guests or families who want to meet with students must first report to the security and head of the cottage and the meeting is specially supervised by security guard